2015
DOI: 10.1158/1541-7786.mcr-14-0645
|View full text |Cite
|
Sign up to set email alerts
|

Decreased eIF3e Expression Can Mediate Epithelial-to-Mesenchymal Transition through Activation of the TGFβ Signaling Pathway

Abstract: The eIF3e protein is a component of the multisubunit eIF3 complex, which is essential for cap-dependent translation initiation. Decreased eIF3e expression is often observed in breast and lung cancer and has been shown to induce epithelial-tomesenchymal transition (EMT) in breast epithelial cells by an unknown mechanism. Here, we study the effect of decreased eIF3e expression in lung epithelial cells by creating stable clones of lung epithelial cells (A549) that express an eIF3e-targeting shRNA. Our data indica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…TGFb controls important EMT markers through both canonical and noncanonical signaling in different cancers (12). Note that EMT not only is regulated through transcription but also is influenced and maintained through interconnected changes in epigenetics (13), micro-RNAs (14), long, noncoding RNAs (15), and protein synthesis (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…TGFb controls important EMT markers through both canonical and noncanonical signaling in different cancers (12). Note that EMT not only is regulated through transcription but also is influenced and maintained through interconnected changes in epigenetics (13), micro-RNAs (14), long, noncoding RNAs (15), and protein synthesis (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Underexpression of eIF3h causes defects in zebrafish embryo development, suggesting that eIF3h could be directly involved in translation initiation of specific transcripts during embryogenesis (Choudhuri et al, 2013). However, our assembly data suggest that these defects could be caused by a loss of function from the inability of downstream subunits to assemble (e.g., eIF3d, e, k, and/or l; Figure 1) into eIF3, which may also be functionally equivalent to downregulating the “unassembled” subunits directly (e.g., eIF3d or e) (Desnoyers et al, 2015; Gao et al, 2015; Li et al, 2015). Alternatively, the defects could be caused by aberrant function of subcomplexes (d,e) or (k,l) unable to assemble in the absence of eIF3h (Figures 1 and 3) (Smith et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…For example, eIF3d and e interact with CDC48 in fission yeast and could alter cell-cycle progression (Otero et al, 2010). The underexpression or truncation of eIF3e has been identified in many breast cancers (Desnoyers et al, 2015; Gillis and Lewis, 2013; Mayeur and Hershey, 2002). In our model, reduction of eIF3e levels in the cell would prevent eIF3d from assembling with eIF3, where it might localize to the nucleus as seen in certain cancers (Uhlen et al, 2005) or activate or repress the translation of certain cell-proliferation transcripts (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that epithelial-mesenchymal transition (EMT) plays a key role in the early process of the metastasis of cancer cells. This process involves the acquisition of the expression of mesenchymal molecules, such as vimentin and N-cadherin, together with the loss of epithelial cell adhesion molecules such as E-cadherin (3,4).…”
Section: Introductionmentioning
confidence: 99%